Ethnographic spectacle and trans-Atlantic performance: Unravelling the costumes of vaudeville's 'Queen', Eva Tanguay. Issue 1 (1st June 2019) - Brayshaw, Emily
Eva Tanguay (1878‐1947), although little known today, was one of the most famous and wealthy actresses in America in the first three decades of the twentieth century. Tanguay's vaudeville success was built on her playing a wild, racialized, highly sexed, financially and socially emancipated woman, who was nonetheless affectionate and warm. Scholarship to date has considered how Tanguay used the offensive stereotype of the 'Coon' associated with African Americans to achieve her huge commercial success, but less attention has been paid to how she used the symbolism and materiality of her costumes in conjunction with her racialized appearance and comportment to achieve her stardom. This article, therefore, examines how Tanguay expressed her 'wild' persona using costumes and comportment that blended established stereotypes that her audiences associated with the era's dime museums, natural history museums, circuses, ethnographic expositions, human zoos and the conventions of minstrelsy. This article also reveals that Tanguay's costumes and comportment were greatly influenced by a popular French performance style, the chanteuse èpileptique. This genre indicated the importance of a bodily comportment which animated costumes that was a highly popular sexualized and racialized performance style associated with cancan dancers that came from France's experiences of ethnographic entertainment. This article thus traces how, as Tanguay's star rose, her performance style increasingly blended trans-Atlantic conventions in costume and comportment to craft a wild persona that expressed the era's tensions around changing gender roles, immigration and race in America.